A Analisis Sikaf Hedonisme Dalam Islam - Edi Marjan Nasution; Ika Merdeka Wati Siregar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
In modern life, consumer behavior is increasingly escalating, often disregarding the boundaries of sufficiency. Such consumption patterns tend toward *tabzir* (extravagance)—a trait deeply detested by Allah (SWT). This study aims to explore the principles of moderation in Islam and the concept of simplicity taught by the religion. It employs a library research methodology, relying on a collection of relevant literature as its primary foundation. The study utilizes both normative and sociological approaches: it is grounded in the Quran and Sunnah, analyzes the perspectives of various figures regarding the subject matter, and seeks to understand the relevant social phenomena. Keywords: hedonism, simplicity, consumption, and society.